EVALUASI DESAIN INSTALASI PENGOLAHAN AIR PDAM IBU KOTA KECAMATAN PRAMBANAN KABUPATEN KLATEN - Arifiani, Nur Fajri; Hadiwidodo, Mochtar (Universitas Diponegoro, 2007)
To supply good water quality, quantity, and continuity is needed an Water Treatment Plant (WTP). The unit process and operation is dependent on quality of water resources. WTP in Klaten Unit Prambanan had a design flow of 20 L/s and had quality of water resources which is more than water parameter regulation. There are ferrous (3,36 mg/L), mangan (0,58 mg/L), colour (159 TCU), and bad odour. So, it is needed aeration, koagulation, flocculation, sedimentation, and filtration units to separate them. Quality of water efluent in this WTP is less than water parameter regulation. There are ferrous (0,18 mg/L) , mangan (0,21 mg/L), colour (3 TCU), and no odour. But, its need more improvement to optimalize reducing parameters.